CONSIDERING WILLIAM JAMES' CONCEPT OF RELIGION FOR TOLERANCE RELIGIOUS GOVERNANCE MODEL IN INDONESIA - Roni Ismail (Religi: Jurnal Studi Agama-agama, 2026)
According to its constitution (Article 29, Paragraphs 1 and 2), Indonesia guarantees every citizen the right to practice a religion and worship according to their respective beliefs. However, there are organized religions, tribal or local religions, and belief systems (aliran kepercayaan) whose religious rights are not guaranteed, experiencing restrictions and even repression in practicing their faith. One cause of this anomaly is the definition of religion used as the basis for policy in Indonesia. Religion is still narrowly defined, characterized by an Abrahamic religion lens, as a "principle of belief in God and a set of worship rules, possessing a holy book and a messenger".  Under this concept, Indonesia only recognizes six official religions with full religious and administrative guarantees. Consequently, many tribal religions and belief systems are excluded, failing to receive religious and administrative rights. Indonesia currently adheres to a religious diversity governance model known as Non-Constitutional Pluralism (NOCOP). A concept of religion as a collective name—rather than a dogmatic one—is needed, considering the sociology, anthropology, and psychology of the Indonesian people. The concept of religion in William James' psychology of religion, defined as "the feelings, acts, and experiences of individual men in their solitude, so far as they apprehend themselves to stand in relation to whatever they may consider the divine," is relevant for use. This definition is open, broad, and non-dogmatic, thus covering all official and unofficial religions, tribal/local religions, and various belief systems in God Almighty. This concept allows Indonesia to shift toward a Constitutional Pluralism model, ensuring that all religions and beliefs are guaranteed their rights to practice, education, house of worship assistance, and other administrative rights. Keywords: Concept of religion, William James' psychology of religion, religious governance, constitutional pluralism.   Indonesia dalam konstitusinya Pasal 29 Ayat 1 dan 2 menjamin setiap warga negara untuk memeluk agama dan beibadat menurut kepercayaannya masing-masing. Akan tetapi, ada agama-agama (organized religion), agama suku atau lokal, dan aliran-aliran kepercayaan tidak terjamin hak-hak beragamanya, mengalami rekstriksi bahkan represi dalam beragama dan beribadat menurut agamanya. Salah satu penyebab anomali ini adalah definisi agama yang dijadikan dasar kebijakan di Indonesia. Agama masih didefinisikan secara sempit dan bercorak Abrahamic religion sebagai “prinsip kepercayaan kepada Tuhan dan tata aturan peribadatan, yang memiliki kitab suci dan utusan”. Dengan konsep ini, Indonesia hanya mengakui enam agama resmi dengan segala jaminan dan hak-hak keagamaan dan admisntratif lainnya. Akan tetapi, banyak agama suku dan aliran kepercayaan tidak dapat tercakup di dalamnya sehingga tidak mendapatkan hak keberagamaan dan hak-hak administratif lain. Indonesia masih menganut governansi keragaman beragama Non-Constitutional Pluralism (NOCOP). Diperlukan konsep agama sebaai nama kolektif, bukan dogmatis, yang mempertimbangkan sosiologi, antropologi dan psikologi bangsa Indonesia. Konsep agama dalam psikologi agama William James sebagai “segala perasaan, tindakan, dan pengalaman manusia secara individual dalam hubungannya dengan apapun yang dipandang Ilahi” relevan digunakan. Ia bersifat terbuka, luas dan tidak dogmatis sehingga bisa mencakup semua agama resmi, agama tidak resmi, agama-agama suku atau lokal, dan aneka aliran kepercayaan kepada Tuhan Yang Maha Esa. Konsep agama James ini relevan untuk governansi keragamaan agama di Indonesia, dan memungkinkan Indonesia menerapkan model Non-Constitutional Pluralism (NOCOP) agar semua agama dan aliran kepercayaan di Indonesia terjamin hak keberagamaan, pendidikan, bantuan rumah ibadah, dan hak-hak administratif lainnya. Kata Kunci: Konsep agama, psikologi agama William James, governansi agama, constitutional pluralism